(untitled) (Konferensiyalar | Conferences, 2024)
This article deals with the importance of teaching reading in language universities. Develops fluency simply by finding a quiet spot and practicing a text several times through, the reality is that there needs to be a coach to model, guide, and encourage in order to make that practice as valuable as possible. Below we identify the various direct instructional roles taken by a teacher or coach in nurturing reading fluency.